The longitudinal relationship between behavior and emotional disturbance in young people with intellectual disability and maternal mental health - Gray, Kylie M (2011)
Although elevated rates of parent psychosocial distress have been associated with child behavior and emotional problems, little is known about the nature of this relationship over time. This study followed an epidemiological cohort of children and adolescents over 11 years with 4 waves of data collection. Within this cohort, complete data were available on 238 mothers and their children. Behavior and emotional problems were assessed using the DBC, maternal mental health with the GHQ. Multivariate growth curve modelling was used to evaluate the commonality of individual change patterns. High levels of mental health problems were reported, which were stable over time. Higher scores on the DBC were associated with higher rates of mental health problems. Increases in child social relating problems were associated with increases mental health symptoms, particularly depression and anxiety.